2017
DOI: 10.1088/1361-6552/aa6c1d
|View full text |Cite
|
Sign up to set email alerts
|

First-year university Physics students’ knowledge about direct current circuits: probing improvement in understanding as a function of teaching and learning interventions

Abstract: Probing university students' understanding of direct-current (DC) resistive circuits is still a field of active physics education research. We report here on a study we conducted of this understanding, where the cohort consisted of students in a large-enrollment first-year physics module. This is a noncalculus based physics module for students in the life sciences stream. The study involved 366 students enrolled in the physics (bio) 154 module at Stellenbosch University in 2015. Students' understanding of DC r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
2
1
Order By: Relevance
“…Analyzing a negative t-value requires considering its absolute value in comparison with the value on the table of t-values and degrees of freedom, which quantifies the variability of the final estimated number. In this case, the absolute value of the experimental t-value of −1.785 is smaller than the value (t = 2.201, p = .05) found on the degrees of freedom chart (11). This fact enables us to state that the mathematical means of the two groups are significantly different.…”
Section: G M Oghlu Sharifovcontrasting
confidence: 55%
See 1 more Smart Citation
“…Analyzing a negative t-value requires considering its absolute value in comparison with the value on the table of t-values and degrees of freedom, which quantifies the variability of the final estimated number. In this case, the absolute value of the experimental t-value of −1.785 is smaller than the value (t = 2.201, p = .05) found on the degrees of freedom chart (11). This fact enables us to state that the mathematical means of the two groups are significantly different.…”
Section: G M Oghlu Sharifovcontrasting
confidence: 55%
“…Newman et al [11] investigated university students' understanding of direct current, and reported that the students' average score on the post-test reveals an enhancement of their learning on the subject of direct-current circuits after using the Circuit app using iPads.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the literature is rich in terms of the studies on the teaching and learning of topics related to electricity. A significant number of these studies are designed specifically with direct current and direct current circuits in mind [5][6][7][8][9][10][11][12]. Many studies on direct current found that students of various levels of learning harbor a range of alternative concepts on the matter, and experience difficulties in learning [9,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%